Prioritising Prosecutions is the Wrong Approach - D’Adamo, Kate (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’